A challenge to identify an optical counterpart of the gravitational wave event GW151226 with Hyper Suprime-Cam. (8th December 2017) - Utsumi, Yousuke; Tominaga, Nozomu; Tanaka, Masaomi; Morokuma, Tomoki; Yoshida, Michitoshi; Asakura, Yuichiro; Finet, François; Furusawa, Hisanori; Kawabata, Koji S; Liu, Wei; Matsubayashi, Kazuya; Moritani, Yuki; et al.
Abstract: We present the results of detailed analysis of an optical imaging survey conducted using the Subaru/Hyper Suprime-Cam (HSC) that aimed to identify an optical counterpart to the gravitational wave event GW151226. In half a night, the i - and z -band imaging survey by HSC covered 63.5 deg 2 of the error region, which contains about 7% of the LIGO localization probability, and the same field was observed in three different epochs. The detectable magnitude of the candidates in a differenced image is evaluated as i ∼ 23.2 mag for the requirement of at least two 5 σ detections, and 1744 candidates are discovered. Assuming a kilonova as an optical counterpart, we compare the optical properties of the candidates with model predictions. A red and rapidly declining light curve condition enables the discrimination of a kilonova from other transients, and a small number of candidates satisfy this condition. The presence of stellar-like counterparts in the reference frame suggests that the surviving candidates are likely to be flare stars. The fact that most of those candidates are in the galactic plane, | b | < 5°, supports this interpretation. We also check whether the candidates are associated with the nearby GLADE galaxies, which reduces the number of contaminants even with a looser color cut. When a better probability map (with localization accuracy of ∼50 deg 2 ) is available, kilonova searches of up to approximately 200 Mpc will become feasible by conducting immediate follow-up observations with an interval of 3–6 d.